REFORMASI HUKUM PIDANA MELALUI PENGATURAN DELIK PERZINAAN DALAM KUHP BARU: PERSPEKTIF PERLINDUNGAN HUKUM KORBAN - Mara Ongku Hsb; Nurpelita Sembiring (Universitas Tabanan, 2026)
Adultery is one of the crimes listed in the Criminal Code that has attracted the most attention, particularly Articles 411 and 412 of the new Criminal Code. According to Human Rights Minister Supratman in his press conference, there are not many differences between the old and new Criminal Codes. One of them is married under the previous Criminal Code, but the new Criminal Code is even though there is no bond because it concerns children, who need to be protected. The research method used in this study is library research, which involves reviewing studies through library data related to the New Criminal Code regarding complaint-based offenses. Research Findings: Legal protection for victims in the new Criminal Code is regulated in Articles 411 and 412, allowing victims to file complaints directly with the authorities. In the old Criminal Code, complaint-based offenses were limited to married individuals, whereas in the new Criminal Code, offenses involving unmarried individuals (cohabiting couples) can be reported by parents and children, which are classified as absolute complaint-based offenses.